HUBUNGAN ANTARA KETERLIBATAN KERJA DENGAN TURNOVER INTENTION PADA KARYAWAN PT. GARDA TRIMITRA UTAMA, JAKARTA - Roni Faslah (Fakultas Ekonomi Universitas Negeri Jakarta, 2010)
ABSTRACTThe purpose of this research is to get a valid and reliable data or fact, to know the correlations between job involvement with turnover intention to employee PT. Garda Trimitra Utama, Jakarta.The analysis test by finding regression equation, that is Ŷ = 75,304 – 0,238X. For regression significance test and the result is, Fcount (5,94) > Ftable (4,03). Showing that, it has significance regression. While regression linearity test, Fcount (1,54) < Ftable = (1.96), showing that regression is linear. The result of product moment of correlations coefficient test, is rxy = -0,231 continued by using correlations coefficient significance test with t-test. Counting result is, tcount(-1,73) < -ttable (-1,67). It means that there are significance and negative correlations between job involment with turnover intention.Beside that, the result of determination coefficient test is 5,34%, it means that turnover intention to employee variable determined by 5,34% job involvement variable. The conclusion of the research have shown that there is a negative correlations between job involvement with turnover intention to employee.Keywords: correlation, job involvement, trunover intention, survey, regression.